(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
The war for talent is a reality of the business environment that companies face today. Given this complex scenario, companies have assumed the need to implement strategies aimed at improving human capital management. Most noteworthy is the new practice of employer branding which enables companies to define their employer brand in order to attract and retain the best talent, as a result of applying Marketing techniques to the field of Human Resources. The results obtained so far show that employer branding is not only effective as a talent management policy, but also benefits the overall performance of the company. This paperaims, by reviewing the existing literature on the subject, to analyze the basic theoretical concepts around which the phenomenon of employer branding is based as well as its practical implications, all in relation to the policies for attracting and retaining human resources in order to contribute to a deeper understanding of a concept that still needs to be defined precisely.